2010
DOI: 10.1212/wnl.0b013e3181cec45c
|View full text |Cite
|
Sign up to set email alerts
|

MRI criteria for MS in patients with clinically isolated syndromes

Abstract: In recent years, criteria for the diagnosis of multiple sclerosis (MS) have changed, mainly due to the incorporation of new MRI criteria. While the new criteria are a logical step forward, they are complex and-not surprisingly-a good working knowledge of them is not always evident among neurologists and neuroradiologists. In some circumstances, several MRI examinations are needed to achieve an accurate and prompt diagnosis. This provides an incentive for continued efforts to refine the incorporation of MRI-der… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
141
0
8

Year Published

2010
2010
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 226 publications
(153 citation statements)
references
References 32 publications
4
141
0
8
Order By: Relevance
“…This revised version increased the sensitivity of the critieria and simplified the features of both DIS and DIT, while maintaining the specifi city of the earlier 2001 and 2005 versions of the criteria (Table 1). 7,[11][12][13][14] The benefits of the 2010 McDonald MRI criteria included the focus on lesion location rather than lesion count, which facilitates MRI interpretation; the elimination of a mandatory interval between the clinical attack and baseline reference scan (which had been arbitrarily determined), thereby facilitating management of patients; and the acceptance of the concomitant presence of gadolinium-enhancing and gadolinium-nonenhancing lesions as evidence for DIT, which allows very early diagnosis in some patients who undergo a single MRI examination at any time after symptom onset.…”
Section: Discussionmentioning
confidence: 99%
“…This revised version increased the sensitivity of the critieria and simplified the features of both DIS and DIT, while maintaining the specifi city of the earlier 2001 and 2005 versions of the criteria (Table 1). 7,[11][12][13][14] The benefits of the 2010 McDonald MRI criteria included the focus on lesion location rather than lesion count, which facilitates MRI interpretation; the elimination of a mandatory interval between the clinical attack and baseline reference scan (which had been arbitrarily determined), thereby facilitating management of patients; and the acceptance of the concomitant presence of gadolinium-enhancing and gadolinium-nonenhancing lesions as evidence for DIT, which allows very early diagnosis in some patients who undergo a single MRI examination at any time after symptom onset.…”
Section: Discussionmentioning
confidence: 99%
“…34 Subjects self-reported of being of European descent. Each individual signed the informed consent document approved by the Institutional Review Board of Partners Healthcare.…”
Section: Study Participantsmentioning
confidence: 99%
“…3,[5][6][7] In the clinical setting, it is highly relevant that GM abnormalities in MS can be visualized in vivo: first, because GM abnormalities strongly explain cognitive and physical disability, 8,9 and second, because focal GM lesions are rather specific for MS. They already occur in the earliest stages of the disease, 10,11 and it was suggested that the McDonald criteria for the diagnosis of MS-at present completely based on WM lesion detection 1,12 -will be of increased accuracy when cortical GM lesions are included. 13 Due to a higher SNR with increased spatial resolution, MS lesion detection has improved by moving from 1.5T MR imaging to 3T.…”
mentioning
confidence: 99%